Bio‐Organometallic Derivatives of Antibacterial Drugs. Issue 30 (18th March 2019) - Sierra, Miguel A.; Casarrubios, Luis; de la Torre, María C.
Abstract: Overuse and misuse of antibacterial drugs has resulted in bacteria resistance and in an increase in mortality rates due to bacterial infections. Therefore, there is an imperative necessity of new antibacterial drugs. Bio‐organometallic derivatives of antibacterial agents offer an opportunity to discover new active antibacterial drugs. These compounds are well‐characterized products and, in several examples, their antibacterial activities have been studied. Both inhibition of the antibacterial activity and strong increase in the antibiotic activity of the parent drug have been found. The synthesis of the main classes of bio‐organometallic derivatives of these drugs, as well as examples of the use of structure–activity relation (SAR) studies to increase the activity and to understand the mode of action of bio‐organometallic antimicrobial peptides (BOAMPs) and platensimicyn bio‐organometallic mimics is presented in this article. Abstract : New opportunities : Misuse of antibacterial drugs has resulted in a significant increase in mortality rates due to bacterial infections and in a pressing necessity of new antibacterial drugs (see figure). Bio‐organometallic compounds offer an opportunity to discover new active antibacterial drugs.